The love elixir of Augusta Stern : a novel - Loigman, Lynda Cohen (St. Martin's Press, 2024)
"It's never too late for new beginnings. On the cusp of turning eighty, newly retired pharmacist Augusta Stern is adrift. When she relocates to Rallentando Springs-an active senior community in southern Florida-she unexpectedly crosses paths with Irving Rivkin, the delivery boy from her father's old pharmacy-and the man who broke her heart sixty years earlier. As a teenager growing up in 1920's Brooklyn, Augusta's role model was her father, Solomon Stern, the trusted owner of the local pharmacy and the neighborhood expert on every ailment. But when Augusta's mother dies and Great Aunt Esther moves in, Augusta can't help but be drawn to Esther's curious methods. As a healer herself, Esther offers Solomon's customers her own advice-unconventional remedies ranging from homemade chicken soup to a mysterious array of powders and potions. As Augusta prepares for pharmacy college, she is torn between loyalty to her father and fascination with her great aunt, all while navigating a budding but complicated relationship with Irving. Desperate for clarity, she impulsively uses Esther's most potent elixir with disastrous consequences. Disillusioned and alone, Augusta vows to reject Esther's enchantments forever. Sixty years later, confronted with Irving, Augusta is still haunted by the mistakes of her past. What happened all those years ago and how did her plan go so spectacularly wrong? Did Irving ever truly love her or was he simply playing a part? And can Augusta reclaim the magic of her youth before it's too late?"--